Argumentacion dialógica textual y contextual en el marco de la justicia transicional en Colombia (2019)
This article seeks to analyze the incidence of Transitional Justice in Colombia in the scenario of Constitutional Dialogue in the guarantees of non-repetition from the implementation of the Special Agreement for Peace. In this sense, a fieldwork was elaborated through structured surveys to the inmates of the Penitentiary and Prison Establishment of High Security with Maximum Security of Combita Boyacá EPAMSCASCO of the National Penitentiary and Prison Institute INPEC and different sectors of the Colombian society.